Ответ:
Объяснение:
-100x^5y^9*(0,3xy^4)² pri x=2 , y=-1
-100x^{5}y^{9}*(0,3xy^{4})²=-100x^{5}y^{9}*(0,09x²y^{8}=
=-9x^{7}y^{17}
-9x^{7}y^{17}=-9x^{7}y^{17}=-9*2^{7}(-1)^{17}=-9*4*(-1)=36
3)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
-100x^5y^9*(0,3xy^4)² pri x=2 , y=-1
-100x^{5}y^{9}*(0,3xy^{4})²=-100x^{5}y^{9}*(0,09x²y^{8}=
=-9x^{7}y^{17}
-9x^{7}y^{17}=-9x^{7}y^{17}=-9*2^{7}(-1)^{17}=-9*4*(-1)=36
Ответ:
3)![-100 * 2^5 * ( -1 )^9 * ( 0,3 * 2 * ( -1 )^4 )^2 = -100 * 2^5 * ( -1 ) * ( 0,3 * 2 * 1 )^2 = -100 * 2^5 * ( -1 ) * ( 0,3 * 2 )^2 = 100 * 2^5 * 0,3^2 * 4 = 100 * 2^5 * ( \frac{3}{10} )^2 * 2^2 = 100 * 2^5 * \frac{9}{100} * 2^2 = 2^5 * 9 * 2^2 = 9 * 2^7 = 9 * 128 = 1152 -100 * 2^5 * ( -1 )^9 * ( 0,3 * 2 * ( -1 )^4 )^2 = -100 * 2^5 * ( -1 ) * ( 0,3 * 2 * 1 )^2 = -100 * 2^5 * ( -1 ) * ( 0,3 * 2 )^2 = 100 * 2^5 * 0,3^2 * 4 = 100 * 2^5 * ( \frac{3}{10} )^2 * 2^2 = 100 * 2^5 * \frac{9}{100} * 2^2 = 2^5 * 9 * 2^2 = 9 * 2^7 = 9 * 128 = 1152](https://tex.z-dn.net/?f=-100%20%2A%202%5E5%20%2A%20%28%20-1%20%29%5E9%20%2A%20%28%200%2C3%20%2A%202%20%2A%20%28%20-1%20%29%5E4%20%29%5E2%20%3D%20-100%20%2A%202%5E5%20%2A%20%28%20-1%20%29%20%2A%20%28%200%2C3%20%2A%202%20%2A%201%20%29%5E2%20%3D%20-100%20%2A%202%5E5%20%2A%20%28%20-1%20%29%20%2A%20%28%200%2C3%20%2A%202%20%29%5E2%20%3D%20100%20%2A%202%5E5%20%2A%200%2C3%5E2%20%2A%204%20%3D%20100%20%2A%202%5E5%20%2A%20%28%20%5Cfrac%7B3%7D%7B10%7D%20%29%5E2%20%2A%202%5E2%20%3D%20100%20%2A%202%5E5%20%2A%20%5Cfrac%7B9%7D%7B100%7D%20%2A%202%5E2%20%3D%202%5E5%20%2A%209%20%2A%202%5E2%20%3D%209%20%2A%202%5E7%20%3D%209%20%2A%20128%20%3D%201152)
Объяснение: